ANALISIS PENDAPATAN USAHATANI JAGUNG MANIS DI KELURAHAN TANI AMAN KECAMATAN LOA JANAN ILIR KOTA SAMARINDA (Analysis of Income of Sweet Corn Farming in Tani Aman Urban Village Loa Janan Ilir Subcity Samarinda City) - ANIS PATMAWATI; MUHAMMAD ERWAN SURIAATMAJA; NIKE WIDURI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2021)
Corn plants are very well known by the people of Indonesia, even in some areas it is used as a staple food. One type of corn plants that people like is sweet corn. The aim of this study were to determine the income obtained by farmers in sweet corn farming. This research was conducted in Tani Aman Urban Village, Loa Janan Ilir Subcity, Samarinda City, with a total sample of 24 people. The data collected were primary and secondary data. The results of this study indicate that the amount of sweet corn farming income was IDR293,438,733.33 cropping season (cs)-1 with an average of IDR12,226,613.89 cs-1 respondent-1. The value of R/C ratio of 2.1 indicates that sweet corn farming is profitable to cultivate.